2017
DOI: 10.12998/wjcc.v5.i9.349
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention of cardiovascular disease in older adults in China

Abstract: Over the past two decades, the percentage of Chinese who is 60 years or older has increased from 5.2% in 1995 to 10.5% in 2015. Approximately 16% of the population in China was 60 years old and above in 2015. Since 1990, cardiovascular disease (CVD) has been the leading cause of death in China. Cardiovascular medications of older adults are usually more complicated than younger age groups due to polypharmacy, the presence of comorbidities and more susceptible to treatment-related adverse outcomes. Therefore, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 80 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…CVD is a class of diseases which are related to the heart or blood vessels including stroke, heart failure, hypertension, coronary artery diseases, heart arrhythmia, peripheral artery disease, and atherosclerosis [1]. Individuals with CVD are found to have the accompanying raised blood pressure, elevated glucose, smoking, obesity, lack of exercise, excessive alcohol consumption, and dyslipidemia.…”
Section: Cardiovascular Diseases: Prevalence and Risk Factorsmentioning
confidence: 99%
“…CVD is a class of diseases which are related to the heart or blood vessels including stroke, heart failure, hypertension, coronary artery diseases, heart arrhythmia, peripheral artery disease, and atherosclerosis [1]. Individuals with CVD are found to have the accompanying raised blood pressure, elevated glucose, smoking, obesity, lack of exercise, excessive alcohol consumption, and dyslipidemia.…”
Section: Cardiovascular Diseases: Prevalence and Risk Factorsmentioning
confidence: 99%
“…The incidence of cardiovascular disease (CVD) is still increasing worldwide, especially in low- and middle-income countries, and CVD remains the leading cause of death in China and worldwide [ 1 2 ]. According to relevant reports, CVD is likely to cause 23.3 million deaths by 2030 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases and cognitive decline share common risk factors including high blood pressure, which was found to be a predictor for CI/MCI among older adults (32, 34). A cross-sectional study (aged 60+ in Beijing) reported a higher prevalence of MCI among hypertensive individuals and also the prevalence of MCI was lower in those treated than in those not treated (18).…”
Section: Resultsmentioning
confidence: 99%